2012
DOI: 10.1111/j.1468-5957.2012.02283.x
|View full text |Cite
|
Sign up to set email alerts
|

Which Competitive Efforts Lead to Future Abnormal Economic Rents? Using Accounting Ratios to Assess Competitive Advantage

Abstract: Strategy theory suggests that firms can impede mean reversion of economic rents by employing competitive efforts, thereby impacting profitability, forecasting, and valuation. We use realized operating performance to establish which competitive effort proxies effectively protect rents. The inclusion of competitive advantage proxies improves future accounting return forecasts and several efforts generalize across industries including power over suppliers and the credible threat of expected retaliation (Porter, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 71 publications
0
12
1
Order By: Relevance
“…Managerial efficiency also has a statistically significant positive relationship with profitability (Jamali and Asadi, 2012). Capital intensity shows a statistically significant positive relationship with profitability, supporting Goldar & Aggarwal (2005) and varying from Dickinson & Sommers (2012).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Managerial efficiency also has a statistically significant positive relationship with profitability (Jamali and Asadi, 2012). Capital intensity shows a statistically significant positive relationship with profitability, supporting Goldar & Aggarwal (2005) and varying from Dickinson & Sommers (2012).…”
Section: Discussionmentioning
confidence: 77%
“…Chowdhury and Amin (2007), , Hirsch, Schiefer, Gschwandtner, and Hartmann (2014) and Zaid et al (2014) also found the same result, while Sur and Chakraborty (2011) found no significant relationship, and Eljelly 2004 Capital-intensive industries are required to take a high level of investment in fixed assets for starting up a business as well as for their overall functioning (Pervan et al, 2019). Goldar and Aggarwal (2005) found a positive relationship between capital intensity and profitability, while Dickinson and Sommers (2012) found a negative relationship.…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…Consequently, more capital-intensive industries may have a higher level of price-cost margins in comparison to less capital-intensive industries (Strickland & Weiss, 1976;Domowitz, Hubbard, & Petersen, 1986a;Prince & Thurik, 1993;Go, Kamerschen, & Delorme, 1999, Goldar & Aggarwal, 2005. However, at the mature phase of the industry, due to excess capacity capital investments could negatively affect profitability (Lieberman, 1987;Dickinson & Sommers, 2012).…”
Section: Capital Intensitymentioning
confidence: 99%
“…Dickinson and Sommers (2012), however, find that many competitive advantages do not lead to a sustainable increase in return on net operating assets.A.Curtis et al …”
mentioning
confidence: 92%